Controlled, Bio‐inspired Self‐Assembly of Cellulose‐Based Chiral Reflectors. Issue 7 (30th May 2014) - Dumanli, Ahu Gumrah; Kamita, Gen; Landman, Jasper; van der Kooij, Hanne; Glover, Beverley J.; Baumberg, Jeremy J.; Steiner, Ullrich; Vignolini, Silvia
<x xml:space="preserve">Abstract</x> The self‐assembly process of photonic structures made of cellulose nanocrystals is studied in detail by locally monitoring and controlling water evaporation. Three different stages during the evaporation process are identified. Spectroscopy quantifies the amount of disorder in the fabricated samples. Control of this process enables the selection of a range of different colors starting from the same suspension, providing a facile, sustainable route for the manufacture of structural color. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>